2019
DOI: 10.1200/jop.18.00431
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical and Economic Outcomes of Prophylactic and Acute Pathologic Fracture Treatment

Abstract: INTRODUCTION: Pathologic fractures often contribute to adverse events in metastatic bone disease, and prophylactic fixation offers to mitigate their effects. This study aims to analyze patient selection, complications, and in-hospital costs that are associated with prophylactic fixation compared with traditional acute fixation after completed fracture. MATERIALS AND METHODS: The Nationwide Inpatient Sample database was queried from 2002 to 2014 for patients with major extremity pathologic fractures. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Mosher et al used The Nationwide Inpatient Sample database from 2002-2014 and found that prophylactic fixation was associated with decreased in-hospital mortality, acute renal failure, anemia, and peri- and postoperative blood transfusions. Similarly, prophylactic fixation had a decreased length of stay and total charges (−3,405 USD, p =0.001) compared to acute fracture treatment [ 17 ]. A 2019 article by El Abiad et al used the American College of Surgeons National Surgical Quality Improvement Program database to compare 30-day postoperative outcomes in prophylactic versus postfracture stabilization for metastatic lesions of the long bones and found lower risk of discharge to a facility other than home (OR 0.48, p =0.02), shorter length of hospital stay (IRR = 0.86, p =0.01), and lower risk of major medical complications (OR = 0.64, p < 0.01) compared with postfracture stabilization [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosher et al used The Nationwide Inpatient Sample database from 2002-2014 and found that prophylactic fixation was associated with decreased in-hospital mortality, acute renal failure, anemia, and peri- and postoperative blood transfusions. Similarly, prophylactic fixation had a decreased length of stay and total charges (−3,405 USD, p =0.001) compared to acute fracture treatment [ 17 ]. A 2019 article by El Abiad et al used the American College of Surgeons National Surgical Quality Improvement Program database to compare 30-day postoperative outcomes in prophylactic versus postfracture stabilization for metastatic lesions of the long bones and found lower risk of discharge to a facility other than home (OR 0.48, p =0.02), shorter length of hospital stay (IRR = 0.86, p =0.01), and lower risk of major medical complications (OR = 0.64, p < 0.01) compared with postfracture stabilization [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mosher et al used e Nationwide Inpatient Sample database from Sarcoma 52002-2014 and found that prophylactic fixation was associated with decreased in-hospital mortality, acute renal failure, anemia, and peri-and postoperative blood transfusions. Similarly, prophylactic fixation had a decreased length of stay and total charges (−3,405 USD, p � 0.001) compared to acute fracture treatment[17]. A 2019 article by (a) (b) Imaging of a patient with an unobserved pathologic lesion who went on to complete fracture.…”
mentioning
confidence: 99%
“…Early intervention for patients with metastatic bone disease has been shown to reduce patient morbidity as well as overall cost. 20 A prompt, proactive response has been shown to reduce complication rates, length of stay, need for community care, and overall treatment costs, and this is specifically true of pathologic fracture. 20 A prophylactic approach has shown to be safer and much more cost-effective compared with traditional management, or acute fixation, after a completed fracture.…”
Section: Healthcare Costsmentioning
confidence: 99%
“…20 A prompt, proactive response has been shown to reduce complication rates, length of stay, need for community care, and overall treatment costs, and this is specifically true of pathologic fracture. 20 A prophylactic approach has shown to be safer and much more cost-effective compared with traditional management, or acute fixation, after a completed fracture. 21 Patients are living longer with advances in systemic therapy, targeted therapy, and radiotherapy treatments, thus making durable reconstruction of a metastatic skeletal location more important.…”
Section: Healthcare Costsmentioning
confidence: 99%
“…Large database studies found prophylactic stabilization to be associated with lower odds of adverse events, death, blood transfusion, increased length of hospital stay, and decreased mortality and treatment cost compared to fracture fixation [133,134]. An institutional study found prophylaxis to be associated with less average blood loss, shorter hospital stays, higher likelihood of discharge to home vs. extended care facility, and greater likelihood of support-free ambulation [135].…”
Section: Therapeutic Approaches To Managing Metastatic Bone Diseasementioning
confidence: 99%